2020
DOI: 10.1093/rheumatology/keaa804
|View full text |Cite
|
Sign up to set email alerts
|

Application of the OMERACT synovitis ultrasound scoring system in juvenile idiopathic arthritis: a multicenter reliability exercise

Abstract: Objectives To evaluate the reliability of the OMERACT paediatric ultrasound (US) synovitis definitions and scoring system in JIA. Methods Thirteen sonographers analysed 75 images for the presence/absence of elementary lesions (binary scoring) and for grading synovitis, synovial hypertrophy, effusion and Doppler signals. Static US images of the second metacarpophalangeal joint (MCP-II), wrist, elbow, knee and ankle in JIA pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 23 publications
0
13
0
3
Order By: Relevance
“…This exercise demonstrated good to excellent reliability for B-mode and PDmode views 22 . Most recently, Rossi-Semerano et al 23 reported the reliability of the OMERACT pediatric US synovitis scoring system among 13 pediatric ultrasonographers of diverse subspecialty backgrounds: nine rheumatologists, two pediatricians, and two radiologists with varying degrees of experience. This group used a total of 75 images to evaluate the reliability of feedback following the first and second training exercises noted that careful review of the normal spectrum of sonographic findings related to the degree of skeletal maturation was most helpful.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This exercise demonstrated good to excellent reliability for B-mode and PDmode views 22 . Most recently, Rossi-Semerano et al 23 reported the reliability of the OMERACT pediatric US synovitis scoring system among 13 pediatric ultrasonographers of diverse subspecialty backgrounds: nine rheumatologists, two pediatricians, and two radiologists with varying degrees of experience. This group used a total of 75 images to evaluate the reliability of feedback following the first and second training exercises noted that careful review of the normal spectrum of sonographic findings related to the degree of skeletal maturation was most helpful.…”
Section: Discussionmentioning
confidence: 99%
“…For the scoring systems of the MCP II, wrist, and elbow, they found fair to good reliability for the B-mode and excellent reliability for PD-mode. However, the scoring system used was not joint-specific, which the authors acknowledged 23 . Our study used a larger sample of normal and pathologic images (n=300), including all views recommended in the evaluation of JIA and involved 17 pediatric rheumatology sonographers with different levels of expertise.…”
Section: Accepted Article Accepted Articlementioning
confidence: 99%
“…Enthesis sites evaluated were: Achilles' tendon, plantar fascia, tibial tuberosity, and superior and inferior pole of the patella femoris. The US examination technique and the standard scans were based on published Outcome Measures in Rheumatology (OMERACT) guidelines and on the studies on paediatric musculoskeletal ultrasound (MSUS) available at study entry The findings obtained were reported according to the semiquantitative gray scale for synovitis in children (PedSynS) and semiquantitative scale for power Doppler [13][14][15][16]. Subclinical synovitis was defined in the presence of joint physical examination without arthritis and ultrasonographic examination with grade 2 or 3 synovitis with or without positive PD signal.…”
Section: Ultrasonographymentioning
confidence: 99%
“…The total number of joints with subclinical activity was 22 / 1260 (1.7%). The most affected were knees (13); wrist (6), talus navicular (1), ankle (1) and 2nd MCP (1). Details in Figures 2 -8.…”
Section: Volume 2 | Issue 2 | 77 J Clin Rheum Res 2022mentioning
confidence: 99%
“…Inflammation of tissues and/or vessels of different location and size is a major component of common rheumatological pathologies such as synovitis, enthesitis and vasculitis (1)(2)(3)(4). Metacarpophalangeal (MCP) joints are frequently involved in inflammatory arthritides especially in rheumatoid arthritis (RA), psoriatic arthritis (PsA), and juvenile idiopathic arthritis (5)(6)(7). Additionally, finger arteries are often affected in various types of vasculitides (3).…”
Section: Introductionmentioning
confidence: 99%